Substrate-driven selective mono- and bis-couplings of ortho-(OTf/I/Br) substituted gem-dibromovinylarenes. Issue 3 (13th January 2017) - Rao, Maddali L. N.; Dasgupta, Priyabrata; Islam, Sk Shamim
Abstract : A one-pot approach with the substrate-driven selective and competitive reactivity of ortho -trifloxy, iodo or bromo functionalized gem -dibromovinylarenes was studied under Pd-catalyzed conditions. Abstract : A one-pot approach with the substrate-driven selective and competitive reactivity of ortho -trifloxy, iodo or bromo functionalized gem -dibromovinylarenes was studied under Pd-catalyzed conditions. These investigations provided synthetically important and structurally diverse functional ortho -alkynylbiaryls, ortho -alkynylbromoarenes, arene-1, 2-diynes and diarylmethylidenefluorenes. The adopted protocol involving the in situ generation of 1-bromoalkyne from gem -dibromovinylarenes and their functionalization in pot- and atom-economical couplings employing triarylbismuths furnished a viable synthetic methodology with good to high yields. The present study also unveiled the substrate-driven selective mono- and bis-couplings using palladium catalyzed domino and sequential reaction protocols.